In Search of Our Warrior Mothers : Women Dramatists of the Black Arts Movement - Forsgren, La Donna L. (Northwestern University Press, 2018)
The Black Arts Movement (1965-76) consisted of artists across the United States deeply concerned with the relationship between politics and the black aesthetic. In Search of Our Warrior Mothers examines the ways in which black women playwrights in the movement advanced feminist and womanist perspectives from within black nationalist discourses. La Donna L. Forsgren recuperates the careers, artistic theories, and dramatic contributions of four leading playwrights: Martie Evans-Charles, J.e. Franklin, Sonia Sanchez, and Barbara Ann Teer. Using original interviews, production recordings, playbills, and unpublished manuscripts, she investigates how these women, despite operating within a context that equated the collective well-being of black people with black male agency, created works that validated black women's aspirations for autonomy and explored women's roles in the struggle for black liberation. In Search of Our Warrior Mothers demonstrates the powerful contributions of women to the creation, interpretation, and dissemination of black aesthetic theory, thus opening an interdisciplinary conversation at the intersections of theater, performance, feminist, and African American studies and identifying and critiquing the gaps and silences within these fields. -- Cover page 4.